2022
DOI: 10.1136/bmjopen-2022-065688
|View full text |Cite
|
Sign up to set email alerts
|

Navigator programme for hospitalised adults experiencing homelessness: protocol for a pragmatic randomised controlled trial

Abstract: IntroductionPeople experiencing homelessness suffer from poor outcomes after hospitalisation due to systemic barriers to care, suboptimal transitions of care, and intersecting health and social burdens. Case management programmes have been shown to improve housing stability, but their effects on broad posthospital outcomes in this population have not been rigorously evaluated. The Navigator Programme is a Critical Time Intervention case management programme that was developed to help homeless patients with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…The model relies heavily on on-site case managers to advocate for their clients, and link them to appropriate community-based health and social service resources, ensuring that a wide range of their health needs are being met [ 71 ]. Other research and program evaluations have shown that employing staff such as navigators, youth workers, case managers, and peers who have lived experience of homelessness, within either system can play an important role in helping people experiencing homelessness transition between systems and receive the necessary follow-up and post-discharge care [ 69 , 72 , 73 ]. Overall, establishing inter-organizational staff roles that focus on providing navigational, transitional, and/or peer support have shown to be promising in strengthening healthcare coordination for YEH within these complex and fragmented systems, as seen with the HCH model.…”
Section: Discussionmentioning
confidence: 99%
“…The model relies heavily on on-site case managers to advocate for their clients, and link them to appropriate community-based health and social service resources, ensuring that a wide range of their health needs are being met [ 71 ]. Other research and program evaluations have shown that employing staff such as navigators, youth workers, case managers, and peers who have lived experience of homelessness, within either system can play an important role in helping people experiencing homelessness transition between systems and receive the necessary follow-up and post-discharge care [ 69 , 72 , 73 ]. Overall, establishing inter-organizational staff roles that focus on providing navigational, transitional, and/or peer support have shown to be promising in strengthening healthcare coordination for YEH within these complex and fragmented systems, as seen with the HCH model.…”
Section: Discussionmentioning
confidence: 99%
“…As the deleterious impacts of homelessness become more widely recognized, hospital systems increasingly accept the need to develop interventions to address the specific needs of PEHs [ 10 , 11 ]. Hospitalization represents a unique opportunity during which critical interventions to address social determinants of health can be implemented.…”
Section: Introductionmentioning
confidence: 99%